The effect of relaxation music in reducing symptoms of dental anxiety (Journal Of Educational and Psychological Researches, 2013)
Many behavioral researchers pointed out the importance of relaxation techniques in the treatment of different psychological disorders where find  the importance of these techniques in reducing anxiety and stress and the resulted of behaviors and habits, with the development of these techniques are being used to gain public health, whether mental health or physical or mentality, and one of these techniques is music therapy that reduces tension and anxiety and operates a state of relaxation, which is used in the treatment of  patients of dental clinic.                         Research problem: Research problem Manifested in finding therapeutic way into account the psychological aspect (anxiety and stress)forClients dental clinic and to the extent that is appropriate and importance of physical aspect, because taking the physical aspect and focus on in therapy alone may not be enough as long as the psychological factor that causes the disorder continues in effect.Importance of research and the need for it: We can clarify the following indicators that demonstrate the importance of this research and the need to:• Is an attempt to highlight the importance of relaxing music to relieve anxiety when dental treatment.• Although the capacity and the large subject with its importance but the Arab Research and Studies and local communities in this area are a few when compared to the importance that has in many countries of the world. So to address this issue would increase the theoretical and practical knowledge in the present time and have a new addition to the library in Iraqi which has shortage in such studies    Aim of study:The current research aimed to achieve the following objectives:There are nosignificant differences on (0.05) level in (pluses rate, the high (Systolic) and the low(Diastolic) blood pressure) to thegroup that listen to relaxationmusic and the group that don’t listen to relaxation music during treatment.Border search: The Current work is limited to adult clients from specialized dental clinic in A Specialized health center for Dentistry in AL ElWia, the side of Rusafa in the city of​​Baghdad, for the period from10\3\ 2011 to 10\6\2011 and from both sexes.Methods and subjects:ASample consistsof200clients(males and females) were review patients (100 patients to listen to relaxationmusic and 100 without listening to it).• Divided the sample into two groups and will be measuredblood pressure and pulse rate for both groups. Results:     The results showed the existence of significant differences in blood pressure tension and heart rate among the first group that did not listen to music and the second group listened to music, as explained in detail in Chapter IV of the search. Through results the researchersconcluded that the importance of using relaxation music to relax patients which reduces the severity of anxiety and tension existing in many clients of dental clinics, and it is recommended to cooperation of psychiatrists clinicians, dentists and patients, as well as educate dentists and patients to benefit from psychosocial therapeuticprograms such as behavioral therapy and relaxation using soft music. The research came out at the end a number of recommendations and suggestions.